Structural characteristics of phenylboronic acid-modified astaxanthin ester and its effect on DSS-induced ulcerative colitis by blocking reactive oxygen species and maintaining intestinal homeostasis - Xing Qiao; Hongyan Li; Qun Gao; Zhigao Wang; Jie Xu; Lu Yang; Changhu Xue (Food Science and Human Wellness)
A novel and reactive oxygen species (ROS) responsive astaxanthin phenylboronic acid derivative (AstaD-PBA) was constructed by grafting phenylboronic acid (PBA) onto astaxanthin succinate diester (AstaD), and its chemical structure and physicochemical property were identifi ed. AstaD-PBA could effectively improve the ROS quenching ability in the lipopolysaccharide (LPS)-induced RAW264.7 cell inflammation model. Then, the bioactivity of AstaD-PBA was studied by 4 zebrafi sh ROS-responsive infl ammatory models induced by LPS, copper (Cu2+), high-fat diet, and dextran sodium sulfate (DSS). The results suggest that AstaD-PBA might have high biosafety and the best effect on ulcerative colitis (UC) induced by DSS. Furtherly, AstaD-PBA signifi cantly alleviated and treated weight loss and colonic shrinkage, inhibited infl ammatory cytokines, and maintained microbiota homeostasis to improve UC in C57BL/6J mice. Alistipes and Oscillibacter were expected to be considered UC marker fl ora according to the Metastats analysis and Pearson correlation Mantel test (P < 0.01) of 16S rRNA gene sequencing data. In conclusion, AstaD-PBA has been promised to be a functional compound to improve UC and maintain intestinal microbiota homeostasis.